Water allocation from Hirakud Dam, Odisha, India for irrigation and power generation using optimization techniques. Issue 3 (3rd July 2021) - Rath, Ashutosh; Swain, Prakash Chandra
ABSTRACT: The current research presents a case study of optimal allocation of water for irrigation and power generation at Hirakud reservoir with the application of meta-heuristic algorithm. Hirakud is a multipurpose project, which is situated in the Sambalpur district of Odisha, India. As the inflow to the reservoir is uncertain, it creates difficulties and complexities in dealing with the reservoir operation. In this work, an effort has been made to build a policy for reservoir operation in Hirakud multipurpose reservoir with a view to satisfying the aim of irrigation and hydropower generation. The conventional methods are not suitable to solve these types of problems involving complexity and nonlinearity in demand and supply. The advantages of using evolutionary algorithm for reservoir optimization are that they deal with objective function information and avoid complications associated with determining derivate or other auxiliary information. The optimization techniques like genetic algorithms, particle swarm optimization, ant colony optimization, etc., have been applied to find optimal release for irrigation and hydropower generation. The analysis indicates performance of ACO a meta-heuristics-based algorithm that provides better result as compared to other methods.